Intermolecular "cross-torque": the N4-cytosine propargyl residue is rotated to the "CH"-edge as a result of Watson-Crick interaction - Domingo, Olwen Charlotte; Hellmuth, Isabell; Jäschke, Andres; Kreutz, Christoph; Helm, Mark (Nucleic acids research, 2015)
Propargyl groups are attractive functional groups for labeling purposes, as they allow CuAAC-mediated bioconjugation. Their size minimally exceeds that of a methyl group, the latter being frequent in natural nucleotide modifications. To understand under which circumstances propargyl-containing oligodeoxynucleotides preserve base pairing, we focused on the exocyclic amine of cytidine. Residues attached to the exocyclic N4 may orient away from or toward the Watson–Crick face, ensuing dramatic alteration of base pairing properties. ROESY-NMR experiments suggest a uniform orientation toward the Watson–Crick face of N4-propargyl residues in derivatives of both deoxycytidine and 5-methyl-deoxycytidine. In oligodeoxynucleotides, however, UV-melting indicated that N4-propargyl-deoxycytidine undergoes standard base pairing. This implies a rotation of the propargyl moiety toward the ‘CH’-edge as a result of base pairing on the Watson–Crick face. In oligonucleotides containing the corresponding 5-methyl-deoxycytidine derivative, dramatically reduced melting temperatures indicate impaired Watson–Crick base pairing. This was attributed to a steric clash of the propargyl moiety with the 5-methyl group, which prevents back rotation to the ‘CH’-edge, consequently preventing Watson–Crick geometry. Our results emphasize the tendency of an opposing nucleic acid strand to mechanically rotate single N4-substituents to make way for Watson–Crick base pairing, providing no steric hindrance is present on the ‘CH’-edge.
Im Titel ist die Ziffer 4 hochgestellt
Gesehen am 15.06.2020